(untitled) (Metallurgy and Foundry Engineering, 2018)
This article presents the results of the physical modeling of the continuous casting of steel slabs in a mold. The experiments focused on the assessment of the shape and stability of the liquid mold slag layer, which was reproduced in studies using silicone oil. The experimental tests were carried out for two different geometries of the submerged entry nozzle, two extreme submergence depths of the submerged entry nozzle (0.215 and 0.295 m), and two extreme casting speeds (1.0 and 1.6 m/min) used in industry. For each variant of the experiment, photographic documentation of the oil layer’s behavior was presented and discussed. The research was supplemented with a visualization of the flow structure using a marker for the selected variant of the experiment.